Electronic and optical properties of Quasi-2D nanostructures and exfoliated systems - Meneses Gustin, Diana Mercedes (Universidade Federal de São Carlos, 2017)
This thesis is aiming to study, according to a theoretical approaches, the electronic and optical properties of quasi-2D semiconductor quantum systems. Using the k · p model as basis we obtained a satisfactory set of results that explain certain optical processes, described below, of nanoscale confined systems such as quantum wells or monolayer atoms. The need and the systematic implementation of new and higher levels of approximation from the original electronic structure models also are themes broadly described here. One of the first contributions of this study was the verification of the necessity of a new approach to describe the phonon-carrier interactions in GaAs-based quantum wells beyond the deformation potential theory. Thus, the Frohlich interaction was considered in our model, revealing the existence of phonon assisted couplings between different states in the valence and conduction band, which resulted in significant changes in the electronic structure. The results of this approach, as well as the simulations and new predictions allowed us to explain two intriguing effects: (i) the potential observation of magneto-polarons of light-heavy holes, (ii) the relevance of 2D states as intermediaries in relaxation processes, assisted by phonons, from a 3D structure to a 0D. Another system studied was the two-dimensional molybdenum disulphide (MoS 2 ), in which the carrier scattering depends on perturbation locally induced in the material. One version of the Dirac Hamiltonian for massive particles was used. The scattering processes have been described in terms of the phase shift and the corresponding cross sections. By comparing the results of this model with those obtained using a parabolic dispersion relation with an appropriate effective mass was possible to obtain interesting information regarding the conductivity of both electronic models. The asymptotic regimes of each of the models were also studied, and for low energies, where both dispersions coincide in parabolic bands, the scattering process is dominated by channels with low angular momentum and still result in almost comparable dispersion amplitudes. On the other hand, the differential cross section in the high energy regime has the clear signature of the two scattering relations. The understanding of the electronic dynamics in these systems is promising for the design of structures with desired functionalities, as exemplified by presenting the differential cross sections for different types of scattering centers.
Keywords: Método k.p; Interação elétron-fônon; Espalhamento em duas dimensões; Phase shift; Scattering cross section; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTADOS ELETRONICOS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA